USM RECEIVES BIOMASS POWER PLANT WITH THREE TYPES OF GASIFIERS - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
NIBONG TEBAL, PENANG, 16 May 2017 Universiti Sains Malaysia (USM) looks forward to be among the pioneers in renewable energy upon receiving a biomass power plant within its premises, which has the potential to be an attraction to students and researchers from all over the country.